Better cattle breeds introduced into the Tanzanian national artificial insemination program for improved dairy productivity for smallholder farmers - CGIAR Research Program on Livestock (2019)
Crossbred bulls were introduced into the Tanzanian national artificial insemination (AI) program for the first time, a dramatic shift from previous practice of providing only exotic, purebred semen to dairy farmers. Under the ILRI-led African Dairy Genetic Gains program, genomic and phenotypic data gathered from cows and bulls, combined with digital performance monitoring, has shown that crossbreeds are more productive, adapted to local conditions and require less feed to produce more milk than purebred cows in Tanzanian smallholder farming systems.